Separation anxiety : [large type] a novel - Zigman, Laura (Thorndike press large print basic, 2020)
"Judy never intended to start wearing the dog. But when she stumbled across her son Teddy's old baby sling during a halfhearted basement cleaning, something in her snapped. So: the dog went into the sling, Judy felt connected to another living being, and she's repeated the process every day since. Life hasn't gone according to Judy's plan. Her career as a children's book author offered a glimpse of success before taking an embarrassing nose dive. Teddy, now a teenager, treats her with some combination of mortification and indifference. Her best friend is dying. And her husband, Gary, has become a pot-addled professional "snackologist" who she can't afford to divorce. On top of it all, she has a painfully ironic job writing articles for a self-help website, a poor fit for someone seemingly incapable of helping herself."--